Global Distribution of Anaerobic Ammonia Oxidation (Anammox) Bacteria – Field Surveys in Wetland, Dryland, Groundwater Aquifer and Snow - Wang, Yu; Xu, Liya; Wang, Shanyun; Ye, Fei; Zhu, Guibing (Frontiers in Microbiology, 2019)
The discovery of anaerobic ammonia oxidation (anammox) filled the gaps in our knowledge on microbial nitrogen cycle. Previous studies reported that anammox bacteria were distributed in a wide range of habitats and played significant roles in the global nitrogen cycle. However, most studies focused only on individual ecosystems or datasets. To date, our understanding of how anammox bacteria respond to and distributed in different habitats in a global scale remain unclear. To explore the global distribution of anammox bacteria, samples were collected from different habitats at different locations globally, including wetland, dryland, groundwater aquifer and snow from ten countries across six continents. We then used high-throughput amplicon sequencing targeting the functional gene and generated community profiles. Results showed that Candidatus Brocadia is detected as the dominant genus in a global scale, accounting for 80.0‒99.9% of the retrieved sequences in the different habitats. The Jettenia-like sequences were the second most abundant group accounting for no more than 19.9% of the retrieved sequences in all sites. The samples in dryland, wetland and groundwater aquifer showed similar community composition and diversity with the snow samples being the most different. Deterministic processes seem stronger in regulating the community composition of anammox bacteria, which was supported by the higher proportion explained by local-scale factors. Groundwater aquifers showed high gene abundance and the most complex co-occurrence network among the 4 type of habitats, suggesting that it might be the preferred habitat of anammox bacteria. There is little competition between anammox bacterial species based on co-occurrence analysis. Hence, we could infer that environmental filters such as anaerobic and stable conditions, instead of substrate limitation, may be the vital factors determining the anammox bacteria community. These results provide better understanding on the global distribution of anammox bacteria and the ecological factors affecting their community structuring in diverse habitats.